PENGARUH FAKTOR KEUANGAN TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN PERBANKAN - Davin Maverik; Susanto Salim (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This study aims to determine the effect of financial factors on bond ratings of banking companies listed on the Indonesia Stock Exchange in 2018-2021. A total of 64 samples of banking sector company data during 2018-2021 were taken using a purposive sampling technique. The tool used for data calculation in this study is EViews 12. The results of the independent variable research obtained in this study reveal that leverage has a significant negative effect, liquidity and profitability have a not significant positive effect on bond ratings.